Effect of Shear Creep on Long-Term Deformation Analysis of Long-Span Concrete Girder Bridge. (13th December 2019) - Niu, Yanwei; Tang, Yingying
Abstract : The purpose of this paper is to report on the development of a three-dimensional (3D) creep calculation method suited for use in analyzing long-term deformation of long-span concrete girder bridges. Based on linear creep and the superposition principle, the proposed method can consider both shear creep and segmental multiage concrete effect, and a related program is developed. The effects of shear creep are introduced by applying this method to a continuous girder bridge with a main span of 100 m. Comparisons obtained with the nonshear case show that shear creep causes long-term deformation to increase by 12.5%. Furthermore, the effect of shear creep is proportional to the shear creep coefficient; for a bridge with different degrees of prestress, the influence of shear creep is close. Combined with the analysis of a continuous rigid bridge with a main span of 270 m, the results based on the general frame program suggest that shear creep amplification is multiplied by a factor of 1.13–1.15 in terms of long-term deformation. Moreover, the vertical prestress has little effect on shear creep and long-term deformation. The 3D creep analysis shows a larger long-term prestress loss for vertical prestress at a region near the pier cross section. The relevant computation method and result can be referenced for the design and long-term deformation analysis of similar bridges.